Pengetahuan Remaja tentang Implementasi Mitigasi Bencana pada Kelompok Rentan di Kelurahan Aur Kecamatan Medan Maimun - Asiah, Nur; Sitohang, Nur Asnah; Karo, Evi Indri Br; Adela, Cut Adeya (Jurnal Riset Hesti Medan, 2023)
Disaster events will have an impact on the stability of the social order. Mitigation is structural and non-structural steps taken to limit the adverse impacts caused by natural hazards, environmental damage and technological hazards. Mitigation measures in terms of their nature can be classified into 2 (two) parts, namely passive mitigation and active mitigation. Vulnerable groups in society that must receive priority during a disaster are pregnant women, mothers giving birth and babies. The impact of disasters on pregnant women is abortion and premature birth because mothers easily experience stress, both due to hormonal changes and environmental pressures around them. Children who experience a disaster feel afraid, sad and in pain because they have experienced trauma. Disasters also affect children's future growth and development. Aur village is on the banks of the Deli river which experiences major flooding every year between December and January. Meanwhile, small floods occur starting in September around 5 times every month. This flood hit Lingkungan III and IV. The number of family heads in Lingkungan III is 360 families and in Lingkungan IV is 255 families. This research aims to increase teenagers' knowledge about implementing disaster mitigation in vulnerable groups. Research design that has been use is descriptive. The sampling technique that has been used is total sampling. The number of samples was 23 people. The research data analysis that has been used is descriptive. The research results showed that the majority were 16 years old (73.3%), high school education (93.34%), parents' occupation, housewife (36.6%), source of information about the implementation of disaster mitigation  through this research (66.6 %). The level of knowledge was good (47.8%), sufficient (39.1%) and poor (13%). This research proves that the health education provided can increase teenagers' knowledge about implementation of disaster mitigation for vulnerable groups.